Pengaruh Kebijakan Penggunaan Izin Pinjam Pakai Kawasan Hutan Lindung Untuk Pertambangan Di Kabupaten Morowali - Muhammad Arrifky Komaruddiansyah; Ahmed Farid; Rahmat Mubaroh (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Indonesia, with its wealth of forest resources (SDH) and mineral resources including gold, silver, copper, oil, natural gas, and coal, faces challenges in managing excessive exploitation. Although coal mining significantly contributes to the economy, this activity has resulted in serious environmental impacts, especially in protected forest areas. The Indonesian government has issued various policies to control the use of forest areas by banning mining activities in protected forests. However, conflicts of interest between the mining and forestry sectors still frequently occur, particularly regarding the utilization of mineral and coal resources. There have been numerous conflicts over land rights affecting 4.4 million hectares in the last 30 years, involving disputes between Mining Jurisdiction Areas (WHP) and the forestry sector. In addressing these conflicts of interest, the government has restricted mining permits in the protected forest area of Morowali Regency. Several regulations, such as Forestry Law No. 41 of 1999, Government Regulation No. 71 of 2014 on the Protection and Management of Protected Forest Ecosystems, and Presidential Instruction No. 6 of 2017, provide a strong legal basis for prohibiting mining in protected forest areas. Nevertheless, the government faces limitations in monitoring and enforcing reclamation regulations in Morowali Regency. Some mining companies fail to properly conduct post-mining reclamation, resulting in negative impacts on the environment and surrounding communities. To address these limitations, efforts are needed to strengthen human resource capacity, allocate adequate budgets, foster cross-sectoral cooperation, utilize technology, involve community participation, and impose strict sanctions. Supervision of mining activities in Morowali Regency is carried out by the central government, provincial authorities, and local governments, involving law enforcement agencies. The government also develops an integrated information system to monitor mining activities in protected forest areas. Efforts to rehabilitate and restore degraded protected forests include tree replanting, maintenance, and economic training for communities. Thus, enhancing coordination between the mining and forestry sectors through synergy between the central and local governments, involving civil society and non-governmental organizations, is essential. The strict enforcement of reclamation regulations and awareness campaigns for mining companies can help ensure compliance with principles of sustainable resource management. In the context of economic development, the Indonesian government must continue to improve efforts to manage forest and mining resources. Synergy among related sectors, optimization of supervision, and environmental sustainability and community welfare should be the primary focus to achieve sustainable development.